2006
DOI: 10.1063/1.2185618
|View full text |Cite
|
Sign up to set email alerts
|

Microphase separation in two-dimensional systems with competing interactions

Abstract: The formation of clusters in condition of thermodynamic equilibrium can be easily observed both in two and three dimensions. In two dimensions relevant cases include pattern formation in Langmuir monolayers and ferrofluids, while in three dimensions cluster phases have been observed in colloids and in protein solutions. We have analyzed the problem within the scenario of competing interactions: typically, a short-range attractive interaction against a long-range repulsive one. This simplified approach is sugge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
202
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 120 publications
(215 citation statements)
references
References 29 publications
12
202
1
Order By: Relevance
“…Simulation studies of Fan et al showed that more complicated models, such as lipid recycling, can stabilize nonequilibrium patterns on a flat membrane [19]. Other models for the stabilization of multiple/patterned domains have also been studied including a general competing interaction model [20] and the effects of dipolar repulsion between lipids [21][22][23]. It has been shown that electrostatics are too short-range to account for the many micron length scale we observe in modulated phases [8] To begin modeling the modulated phases we first formulate an energy functional.…”
Section: B Simulation Modelmentioning
confidence: 99%
“…Simulation studies of Fan et al showed that more complicated models, such as lipid recycling, can stabilize nonequilibrium patterns on a flat membrane [19]. Other models for the stabilization of multiple/patterned domains have also been studied including a general competing interaction model [20] and the effects of dipolar repulsion between lipids [21][22][23]. It has been shown that electrostatics are too short-range to account for the many micron length scale we observe in modulated phases [8] To begin modeling the modulated phases we first formulate an energy functional.…”
Section: B Simulation Modelmentioning
confidence: 99%
“…Similarly, in the striped phase in two dimensions the particles are arranged in parallel stripes with low-density regions in between the stripes. 2, 14,18 In three dimensions the stripes form a gel-like network of elongated clusters. 5,15,17 This behavior is most striking given that the pair interactions between the particles are spherically symmetrical and suggests that such systems could be important candidates for developing self-assembling pattern forming materials.…”
Section: Introductionmentioning
confidence: 99%
“…Theory and simulation in both two and three dimensions for model systems with competing interactions predict that such interactions can give rise to a state with undamped periodic density fluctuations, which indicates a transition to cluster or striped phases ͑microphase separation͒. [9][10][11][12][13][14][15][16][17][18] In the cluster phase the colloids are ordered in such a way that there are assemblies containing tens or hundreds of particles and large voids between the clusters containing hardly any particles. Similarly, in the striped phase in two dimensions the particles are arranged in parallel stripes with low-density regions in between the stripes.…”
Section: Introductionmentioning
confidence: 99%
“…To that aim we have analyzed the behavior of a two dimensional fluid with competing interaction ranges whose particles tend to cluster at low temperatures. Our model is a soft core version of the "short-range attractive and long-range repulsive" (SALR) potential first proposed by Sear and coworkers 26 , and analyzed in detail by Imperio and Reatto 27,28 . The clustering properties under disordered confinement of this hard core model have also recently been studied by Schwanzer and Kahl 29 .…”
Section: Introductionmentioning
confidence: 99%